Evaluation of rice mill effluent bioremediated by polyhydroxyalkanoate production on the growth of Broad bean. Funded Research Work - POORNA CHANDRIKA SABAPATHY,; SABARINATHAN DEVARAJ,; PREETHI KATHIRVEL, (International Journal of Pharma and Bio Sciences, 2017)
Treated parboiled rice mill effluent (TRME) was investigated for its utilization in agriculture for the purpose of irrigation. The effluent was treated by the fermentation process of the bacterium Acinetobacter junii BP25 (Genebank Accession no – KY072961) for the production of the biodegradable polymer polyhydroxyalkanoates (PHA). Pot culture experiments were conducted to study the effect of TRME on seed germination, chlorophyll content, total carbohydrate, protein and amino acids of broad bean (Vicia faba, Variety COGB 14) at different time intervals with varying effluent concentrations. TRME was acidic in nature (pH 5 ± 0.5), with comparatively lesser COD (650 ± 1.2 mg/L) and BOD (312 ± 1.6 mg/L) when compared with the effluent before the treatment process (COD- 6250 ± 2.2 mg/L; BOD- 620 ± 2.5 mg/L). The germination percentage of seed and the biochemical parameters showed a gradual decline with increase in effluent concentration. It has been observed that 10% (pH 7 ± 0.5) effluent concentration had positive impact (P < 0.05) on all the parameters of the plant up to 20 days. However, at higher concentrations of TRME, toxic effects were observed after 20th day. This suggests that the neutralized effluent can be used safely for broad bean cultivation, after proper dilution and treatment.